Modelling energy efficiency and generation potential in the South African wastewater services sector - Zvimba, John N (Water science and technology : a journal of the International Association on Water Pollution Research, 2020)
About 55% of energy used in the South African water cycle is for wastewater treatment, with the bulk of this energy associated with aeration in biological processes. However, up to 15% of wastewater energy demand can be offset by energy generation from sludge (power and/or combined heat and power), while best practices adoption can deliver energy efficiency gains of between 5% and 25% in the water cycle. Advanced process modelling and simulation has been applied in this study as a tool to evaluate optimal process and aeration control strategies. This study further applied advanced modelling to investigate and predict the potential energy consumption and consumption cost pattern by the South African wastewater sector resulting from implementation of optimal process and aeration energy use reduction strategies in support of sustainable municipal wastewater management. Aeration energy consumption and cost savings of 9-45% were demonstrated to be achievable through implementation of energy conservation measures without compromising final effluent regulatory compliance. The study further provided significant potential future energy savings as high as 50% and 78% through implementation of simple and complex aeration energy conservation measures respectively. Generally, the model-predicted energy savings suggest that adoption of energy efficiency should be coupled with electricity generation from sludge in order to achieve maximum energy consumption and cost savings within the South African wastewater services sector